Cover Feature: Temperature and Composition Dependent Optical Properties of CdSe/CdS Dot/Rod‐Based Aerogel Networks (ChemPhysChem 2/2022). Issue 2 (19th January 2022) - Rusch, Pascal; Pluta, Denis; Lübkemann, Franziska; Dorfs, Dirk; Zámbó, Dániel; Bigall, Nadja C.
Abstract : The Cover Feature illustrates a network of CdSe/CdS Dot/Rod nanocrystals built up of nanocrystals based on differently sized CdSe quantum dots. The excitonic processes in these networks are investigated in time‐ and temperature‐resolved photoluminescence spectroscopy. More information can be found in the Article by Nadja C. Bigall and co‐workers .